Parameters and Patterns of COVID-19 Pandemic Development in The Border Regions of The Baltic Sea Countries - Michał BILCZAK (Communications of International Proceedings, 2021)
In the study, on the example of the border regions of the Baltic Sea, the methods and tools of crisis phenomena in the conditions of the COVID-19 pandemic are presented. The measures and restrictions introduced on the functioning of the economic subjects have caused shock and stress situation in the border regions, which are of great importance for the course of the crisis conditions and for the way out of the crisis. Banning certain sectors and sectors of the economy, transfer of education to distance technologies and also the new problems identified in the health care system showed that many regional authorities were unable to sustain economic activity, which, in turn, had some negative impact on economic growth and expectations for investment and consumption. This study showed that the authorities were unprepared and, in some cases, unable to address the pandemic with previously available tools and methods. Regional authorities had to seek new ways to adapt and function in a very new and unfamiliar environment. There was an urgent need to identify crises and new challenges that accompany and rapidly evolve in a pandemic. The extent and nature of the impact of temporary border closures in the border regions of the Baltic Sea States are presented. Economic recession can cause some long-term damage and, like the study shows, many firms and businesses may lose jobs, which, in turn, will increase unemployment and, eventually, end up in bankruptcy. The pandemic varies in these regions and therefore the measures taken should contribute to the recovery of lost ground and strengthen cross-border cooperation. The contribution of this paper is that its materials can be used in similar studies.
Keywords: COVID-19 pandemic; border region; cross-border cooperation; corona crisis; Baltic Sea countries